The fortress of the raven : Karak in the Middle Islamic period (1100 -1650) - Milwright, Marcus. (Islamic History and Civilization, 2008)
In c.1142 work started on the construction of a major castle in the southern Jordanian town of Karak. The largest of a network of fortifications, Karak castle became the administrative centre of an important Crusader lordship. After 1188 Karak and its territories were incorporated into the Ayyubid, Mamluk and Ottoman sultanates. This book traces the history of Karak and the surrounding lands during the Middle Islamic period (c.1100-1650 CE). The book offers an innovative methodology, combining primary textual sources (in Latin and Arabic) with archaeological data (principally the ceramic record) as a means to reconstruct the fluctuating economic relations between Karak and other regions of the Middle East and eastern Mediterranean.